Local Knowledge as a Resource for Nepal: Building Partnerships with Scientists and Conservationists - Huntington, Henry P (Conservation Science, 2013)
Conservation cannot be carried out solely by professional biologists and conservationists. This is true everywhere, and perhaps especially in places where professional resources are scarce. There are, however, other resources to draw on for ideas and actions to conserve the environment and the human livelihoods that depend on a healthy environment. The knowledge, experience, and practices of local residents can contribute greatly to conservation efforts, especially in partnership with professionals. Based on recent experiences in rural Nepal, I describe three examples of the potential for such collaboration, which I interpret in part in light of my own work in the Arctic. DOI: http://dx.doi.org/10.3126/cs.v1i1.8577 Conservation Science 2013 1(1), 1–4